Perception Of Early Grade Teachers Of Madrasah Ibtadaiyah Towards Attributes Innovations Of Thematic Learning - Aminah; Robinson Situmorang; M Syarif Sumantri (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Negeri Jakarta, 2023)
Thematic learning is an integrated learning model that links or combines several subjects in one particular theme, in order to make it easier for students to see meaningful relationships, and make it easier for them to understand the material/concept as a whole. This study aims to analyze the perceptions of early grade MI teachers in Bireuen Regency towards thematic learning as an innovation based on its attributes (relative advantage, compatibility, complexity, trialability and observability). This study used a quantitative approach and diffusion research procedures developed by Rogers. The data in this study were collected by giving questionnaires to 29 MI early grade teachers in Bireuen District. The results showed that the thematic learning innovation attributes were relatively positively perceived by MI early grade teachers. Thus thematic learning is perceived to be more profitable (relative advantage) than previous learning models, a high level of compatibility with the values ​​and norms adopted by the community, easy to implement (low level of complexity), trialability (can be tried out) and Early grade MI teachers perceive negatively the observability attribute.